2016
DOI: 10.1186/s12958-016-0142-4
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of betamethasone concentration in maternal serum treated for fetal lung maturity; Is it feasible?

Abstract: BackgroundThe association between maternal serum concentration of betamethasone given for fetal lung maturity and perinatal outcome has not been investigated. This may be due to an absence of a reliable method for measuring serum betamethasone concentrations. We aimed in the current study to assess the feasibility of a specific ELISA kit to measure the concentrations of betamethasone in maternal serum and to examine the trend of sequential measurements after a course of betamethasone for fetal lung maturity.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In the present study, all patients received only a loading dose of nifedipine within 1 hour without a maintenance dose owing to the cessation of uterine contractions. Moreover, the peak plasma concentration of nifedipine is reached after 1 hour and its half‐life is approximately 3 hours, whereas the highest serum concentration of betamethasone is seen 36 hours after the first dose and betamethasone continues to be effective for to 5–7 days in pregnant women . In addition, all women in the present study received the second betamethasone dose 24 hours after the first dose.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the present study, all patients received only a loading dose of nifedipine within 1 hour without a maintenance dose owing to the cessation of uterine contractions. Moreover, the peak plasma concentration of nifedipine is reached after 1 hour and its half‐life is approximately 3 hours, whereas the highest serum concentration of betamethasone is seen 36 hours after the first dose and betamethasone continues to be effective for to 5–7 days in pregnant women . In addition, all women in the present study received the second betamethasone dose 24 hours after the first dose.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, the peak plasma concentration of nifedipine is reached after 1 hour and its half-life is approximately 3 hours, 20 whereas the highest serum concentration of betamethasone is seen 36 hours after the first dose and betamethasone continues to be effective for to 5-7 days in pregnant women. 25 In addition, all women in the present study received the second betamethasone dose 24 hours after the first dose. Therefore, it is suggested that the Doppler parameters in the present study were affected by betamethasone only because patients received only a loading dose of nifedipine and because of the short half-life of nifedipine versus the long duration of betamethasone action.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, according to a previous publication, the concentration diminished gradually to a level close to the baseline at 5–7 days after the first course of betamethasone. 5 Besides, most women who had a rescue dose did not receive it back‐to‐back. Finally, we made a subanalysis restricted to women who received one course only.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, both maternal and neonatal (cord) levels were analyzed using the same Corticosteroid enzyme‐linked immunosorbent assay (ELISA) kit (Randox Laboratories Ltd.). Preliminary results showed that the kit is valid for determining betamethasone concertation 5 . The assay exhibits very low cross‐reactivity for cortisol (<0.5%), which is vital in minimizing interference from endogenous cortisol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation